The Student Perspective Towards Technology Use to Encourage English Speaking Among Non-English Majors - Rifanya Permata Abdi; Anggi Apriani; Chika Rahmadany; Serli Azrena; Wandi Syahfutra; Novela Nurafrezah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dwijendra, 2025)
The integration of technology in language education has introduced innovative approaches to enhancing speaking skills, offering new tools and platforms for learners to engage with the language outside the traditional classroom setting. However, despite the growing presence of digital resources, non-English major students continue to face several challenges in using these technologies effectively to improve their English-speaking skills. Key obstacles include low motivation, limited opportunities for authentic language practice, and insufficient feedback on their performance. This qualitative study explores the perspectives of 20 undergraduate students majoring in management at a university in Indonesia, examining their experiences with various technological tools aimed at enhancing their English-speaking abilities. Data were collected through semi-structured interviews and focus group discussions, which were then analyzed thematically to identify common trends and perceptions. The findings reveal that while technology plays a significant role in increasing students' motivation, accessibility to learning materials, and confidence in speaking, several issues persist. These include technical barriers such as poor internet connectivity, the lack of personalized feedback from language-learning applications, and the insufficient integration of technology within the traditional classroom setup. Furthermore, many students expressed a need for more structured guidance and support from teachers in utilizing these technologies effectively. The study emphasizes the importance of addressing these challenges by developing improved feedback mechanisms within educational technologies and offering comprehensive teacher training programs. These initiatives would help educators better integrate technology into language instruction and provide more tailored support to students. Ultimately, the study highlights that a balanced approach, combining technology with face-to-face interaction, is essential to fully leverage the potential of digital tools for language learning. The insights drawn from this research offer valuable recommendations for educators, policymakers, and developers aiming to optimize the role of technology in enhancing language education, particularly for non-English major students.